2019
DOI: 10.1016/j.esxm.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in Women Treated for Type 1 Diabetes and the Impact of Coexisting Thyroid Disease

Abstract: Introduction More sexual problems are reported among people treated for diabetes; however, this situation is less explored in women than in men. Aim To analyze the presence and causal links of female sexual dysfunction (FSD) among Czech women treated for type 1 diabetes. Methods 40 women completed a national version of the Female Sexual Function Index (FSFI), Female Sexual Distress Scale-revised (FSDS-R), and Beck’s Depression Inventory–II (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…According to recent studies, the prevalence of FSD is higher in patients with DM than in the general population. In women with T1DM, the prevalence of FSD varies between 18 and 71%, and the odds ratio is 2.27 in patients with FSD [ 36 ]. A study performed by Ezlin et al reported that sexual dysfunction was more frequent in women with T1DM than in healthy women (27 vs. 15%), with a predominance of decreased lubrication [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to recent studies, the prevalence of FSD is higher in patients with DM than in the general population. In women with T1DM, the prevalence of FSD varies between 18 and 71%, and the odds ratio is 2.27 in patients with FSD [ 36 ]. A study performed by Ezlin et al reported that sexual dysfunction was more frequent in women with T1DM than in healthy women (27 vs. 15%), with a predominance of decreased lubrication [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrates that m-health interventions addressing sexual problems for patients with chronic diseases have not been considered sufficiently over the last 10 years. Although various chronic diseases such as diabetes, hypertension, inflammatory bowel disease and so on can affect sexual functioning, [38][39][40] reviewed studies mostly considered breast or prostate cancer for female or male patients, respectively, indicating that more research is needed for the evaluation of m-health interventions aiming at sexual health improvement in patients with other chronic disease and considering other types of cancer as well.…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff for depression is 20 [13]. The scoring of BDI II is as follows: 1 -10 = normal; 11 -20 = mild mood disturbances; 20 -25 = borderline clinical depression; 25 -30 = moderate depression; 31-40 = severe depression, and > 40 = extreme depression [14].…”
Section: Beck's Depression Inventory IImentioning
confidence: 99%